mgr-mir-228-regulated transthyretin-like protein in Meloidogyne graminicola suppresses ROS generation and enhances parasitism - Zhongling Tian; Yixiao Cai; Mingming Zhu; Liang Wang; Qiannan Liu; Qinghong Li; Xiaoyi Gao; Jingwu Zheng; Borong Lin; Kan Zhuo; Shaojie Han (Phytopathology Research)
Abstract The transthyretin-like protein family is highly conserved across plant parasitic nematodes, yet its role in Meloidogyne graminicola, a significant plant parasitic nematode in rice, remains underexplored. In this study, we identified and characterized the MgTTL1 gene, which encodes a transthyretin-like protein with a distinctive N-terminal domain predicted to facilitate plasma membrane localization. Expression analysis revealed that MgTTL1 is specifically localized in the esophageal gland cells and is significantly upregulated during the parasitic stages of the nematode. Using deep sequencing data, we identified mgr-mir-228 as a miRNA that interacts with MgTTL1 mRNA, as validated by dual-luciferase reporter assays. Notably, mgr-mir-228 is highly expressed during the J2 stage but downregulated in the J3/J4 stages, likely to suppress MgTTL1 expression before host root invasion, suggesting its potential as a resistance trait in managing root-knot nematodes in rice. Functional assays, including in vitro RNA interference and mgr-mir-228 mimics treatment, demonstrated that reducing MgTTL1 levels impacts nematode reproduction. Overexpression of MgTTL1 in planta resulted in a suppression of reactive oxygen species (ROS) production in response to pathogen-associated molecular patterns, thereby significantly increasing susceptibility to nematode and bacterial pathogens. These findings suggest that MgTTL1, specifically regulated by the newly identified miRNA mgr-mir-228, functions as a negative regulator of ROS-mediated plant immunity and plays a pivotal role in modulating plant susceptibility to nematode infections.